WHY VISITS OF EMERGENCY DEPARTMENT DECREASED DURING THE COVID-19 PANDEMIC? CASE STUDY IN X HOSPITALS, MALANG REGENCY - Kusumawati, Anita Mardiana; widyaningrum, kurnia (Fakultas Kedokteran Universitas Brawijaya)
The visits rate to the Emergency DepartmentofX Hospital in the period April to June 2020, on average, decreased by 45.11% compared to the January - March 2020 period. The study aimed to identify the factors causing the decrease in the number of the Emergency Departmentduring the Covid-19 pandemic at X hospital. This study used a qualitative descriptive approach with Focus Group Discussion (FGD) data collection techniques analyzed using Fishbone Diagram combined with 5 WHYs.The subjects were determined based on purposive sampling, namely 8 respondents consisting of Nurses, Doctors and CoordinatorofEmergency Department, Head of Public Relations and Marketing Unit, Coordinator of Security Guard and Coordinator of Patient Registration Office. The results showed that there were several root causes of the decrease in the number of the Emergency Departmentat Xhospital: Emergency departmentstaffs had difficulty in providing education about Covid-19 screening and isolation care to patients and their families, patients refused further treatment, and patients refused to go to the hospital. Thus the decrease in the number of inpatients of the Emergency Department during the Covid-19 pandemic were caused by various factors, especially the difficulty of Emergency Departmentstaffs in providing education on Covid-19 screening and its subsequent care.